Pathogenic variation in Xanthonomas campestris pv. phaseoli, the causal agent of common bacterial blight in Phaseolus beans - Opio, A.F.; Allen, David J.; Teri, J.M. (Wiley, 1996)
A total of 93 isolates of Xanthomonas campestris pv. phaseoli was collected from five countries over a wide range of altitude (500 2320 m above sea level) in eastern Africa. Collections were made from a range of cultivars of the common bean (Phaseolus vulgaris), including known sources of resistance, as well as from wild alternative but symptomless hosts including Senna (Cassia) hirsuta and Digitaria scalarum. From these, 30 isolates were selected for detailed characterization. Although variation was found in parameters including phage type, the production of brown pigment in culture media and in-vitro growth rate, there was little consistent relationship between these characters and pathogenic variation.